Shoulder injuries in skeletally immature throwers: review and current thoughts - Leonard, J.; Hutchinson, M. R. (British Journal of Sports Medicine, 2010)
The incidence of shoulder injuries in the paediatric athletic population continues to increase with increased participation particularly in throwing and overhead sports. While soft tissue injuries can occur, the physis remains the weak link and site of injury in many cases. Injury prevention targets proper throwing mechanics and the avoidance of overuse injuries by monitoring the amount of training and number of throws these young athletes are exposed to.